Autoinducer-2 promotes Pseudomonas aeruginosa PAO1 acute lung infection via the IL-17A pathway - Li, Hongdong; Li, Xingyuan; Ai, Qing; Tan, Liping (Frontiers in Microbiology, 2022)
Pseudomonas aeruginosa is an opportunistic pathogenic bacterium that causes various acute and chronic lung infections in immunocompromised patients. We previously found that a quorum sensing (QS) signal, namely, autoinducer-2 (AI-2), facilitates the pathogenicity of the wild-type (WT) P. aeruginosa PAO1 strain in vitro and in vivo. However, the immunological mechanism that leads to pulmonary injury remains to be elucidated. In this study, we aimed to investigate the effects of AI-2 on interleukin-17A (IL-17A) production during acute P. aeruginosa PAO1 lung infection using a mouse model, with an emphasis on the underlying immunological mechanism. Compared to infection with P. aeruginosa PAO1 alone, infection with P. aeruginosa PAO1 combined with AI-2 treatment resulted in significantly increased levels of IL-17A, numbers of Th17 cells and levels of STAT3 in the lung tissues of WT mice (P < 0.05), as well as more serious lung damage. In contrast, the concentrations of the proinflammatory cytokines IL-1α, IL-1β, and IL-6 and the chemokine keratinocyte-derived chemokine (KC) were significantly reduced during P. aeruginosa lung infection in IL-17A-/- mice compared with WT mice (P < 0.05), and no effects were observed after AI-2 treatment (P > 0.05). Furthermore, the level of IL-17A in the lungs of WT mice was significantly reduced following infection with a P. aeruginosa strain harboring mutations in the QS genes lasR and rhlR compared with the level of IL-17A following infection with P. aeruginosa PAO1. Our data suggest that AI-2 promotes P. aeruginosa PAO1 acute lung infection via the IL-17A pathway by interfering with the QS systems of P. aeruginosa. IL-17A may be a therapeutic target for the treatment of acute P. aeruginosa lung infections in the clinic.